A TOUCH OF GREY: PERSONAL REFLECTIONS ON TEACHING THE GRATEFUL DEAD TO SENIORS - Trudeau, Robert (Dialogue, 9(1,2), 2022)
This essay reflects on several occasions in which I was a facilitator introducing the music of the Grateful Dead to groups of senior citizens. Several themes emerge: First, there is the need to separate the facilitator’s feelings as a convinced Deadhead from the inclinations of older individuals who know little about the Grateful Dead. Second, an indirect approach that emphasizes lyrics and accessible songs seems to have the best impact, if the goal is to encourage individuals to want to learn more about, and listen to, the Grateful Dead’s music. Third, one should let students construct the framework of the information that they themselves feel they need. Finally, it takes a lot of preparation to be able to improvise in and around the structures students develop. Keywords: Grateful Dead, popular culture, pedagogy
Keywords: Type of access: Open Access